Relationship between selected attacking performance indicators and match dynamics in the FIFA U-20 World Cups 2019 and 2023 - Effendey, F. Z. E. Z.; Zainuddin, N. F.; Miswan, M. S.; Hasan, M. H.; Krasilshchikov, O.; Ghazali, M. (Journal of Physical Education and Sport, 2025)
Youth football plays a crucial role in talent development and tactical evolution, with international tournaments like the FIFA U-20 World Cup showcasing emerging players and innovative strategies. Despite the increasing emphasis on youth football as a talent pipeline, comprehensive analyses of goal-scoring patterns in age-specific tournaments remain limited. In addition, comparing play patterns between World Cup editions may be necessary for understanding playing approaches. This study examines key performance indicators (KPIs) influencing match outcomes in the 2019 and 2023 youth tournaments, focusing on goal-scoring patterns and tactical trends. Utilizing notational analysis, data from 104 matches and 307 goals were analyzed across seven KPIs: goal-scoring zones, assist locations, passing sequences, goal timing, scorer and assist provider positions, goal-scoring mechanisms, and types of play (open play vs. set pieces). Statistical analyses, including independent t-tests and Pearson`s Chi-Square tests, evaluated inter-tournament differences and associations between KPIs and match outcomes. Results revealed that Position 2 (box inside the penalty area) was the predominant goal-scoring zone, while Position 12 (edge outside the penalty area) increased from 8.5% of goals in 2019 to 14.9% in 2023. Position 5 (centre just outside the penalty area) emerged as the primary assist zone in 2023. Headed goals increased significantly from 15.0% to 23.4%, indicating a shift toward aerial strategies. A decline in long-passing sequences highlighted a trend toward direct attacking play, with open play dominating scoring and set-piece contributions marginally decreasing. Notably, goals peaked in the 76-90+ minute interval, with goal timing in 2019 and goal-scoring mechanisms in 2023 showing significant associations with match outcomes. These findings clarify evolving tactical dynamics in elite youth football, offering evidence based on specific indicators such as goal timing and goal-scoring mechanisms. This study informs coaches` understanding and approach toward attacking and defensive strategies based on game situations and match timelines by delineating critical scoring zones, assist patterns, and strategic shifts. Further investigation should focus on the influence of defensive strategies and goalkeeper performance on goal-scoring patterns, as well as changes in attacking tactics and player positioning.